Segment-specific pattern of sympathetic preganglionic projections in the chicken embryo spinal cord is altered by retinoids - Forehand, Cynthia J. (The National Academy of Sciences, 1998)
Sympathetic preganglionic neurons exhibit segment-specific projections. Preganglionic neurons located in rostral spinal segments project rostrally within the sympathetic chain, those located in caudal spinal segments project caudally, and those in midthoracic segments project either rostrally or caudally in segmentally graded proportions. Moreover, rostrally and caudally projecting preganglionic neurons are skewed toward the rostral and caudal regions, respectively, of each midthoracic segment. The mechanisms that establish these segment-specific projections are unknown. Here we show that experimental manipulation of retinoid signaling in the chicken embryo alters the segment-specific pattern of sympathetic preganglionic projections and that this effect is mediated by the somitic mesoderm. Application of exogenous retinoic acid to a single rostral thoracic somite decreases the number of rostrally projecting preganglionic neurons at that level. Conversely, disrupting endogenous synthesis of retinoic acid in a single caudal thoracic somite increases the number of rostrally projecting preganglionic neurons at that level. The number of caudally projecting neurons does not change in either case, indicating that the effect is specific for rostrally projecting preganglionic neurons. These results indicate that the sizes of the rostrally and caudally projecting populations may be independently regulated by different factors. Opposing gradients of such factors along the longitudinal axis of the thoracic region of the embryo could be sufficient, in combination, to determine the segment-specific identity of preganglionic projections.